IMPLEMENTASI KEBIJAKAN PENDIDIKAN ISLAM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN SATU ATAP 10 SAROLANGUN - Ridwan, Ahmad; Madyan, M; Bafadhal, Izhar; Damanik, Jainab Rayanti (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
The purpose of this study is to examine the implementation of Islamic education policies in Islamic Education (PAI) learning at SMPN Satu Atap 10 Sarolangun and to explore the roles of teachers, principals, and the surrounding community in supporting this implementation. This research employed a qualitative approach with field studies conducted at SMPN Satu Atap 10 Sarolangun through observations, interviews, and documentation with selected informants. Data were analyzed using the Miles, Huberman, and Saldaña model with triangulation to ensure the validity of the findings. The results indicate that the implementation of Islamic education policies at SMPN Satu Atap 10 Sarolangun is effectively carried out through the synergy of teachers, principals, and the community. PAI teachers play a central role in both teaching and character development, principals provide policy and managerial support, while the community, particularly parents and religious leaders, reinforces Islamic values through active participation. Despite limited facilities, this collaboration fosters a religious and conducive learning environment in the rural context.